12 month prevalence of nicotine, alcohol and substance dependence among university students - Kaya, Nazmiye; Çilli, Ali Savaş (Journal of Dependence, 2002)
Objective: This study was aimed to determine the 12 month prevalence of nicotine, alcohol and substance dependence among university students according to DSM-IV criteria. Method: Totally 323 randomized students (male/female: 168/155) were interviewed using 12 month version of CIDI 2.1 (Composite International Diagnostic Interview). Results: The ratio of daily smoking of students during a month or more than a month in the past year was 27.5%. Seventeen percent of students had nicotine dependence and 13% had nicotine abstinence. Prevalence of nicotine dependence was significantly higher among male students. Nearly 10.2% of students reported that they had used at least 12 drinks of alcohol in the past year, 1.2% of students had alcohol dependence and 2.2% had alcohol abuse. None of the students had substance abuse or dependence. Conclusion: Nicotine dependence is one of the most important health problems among college students. Alcohol related disorders also should be considered as an important problem. The reason why we could not detect any substance use disorder might be that subjects did not declared substance use for these substances are illegal or it might be a cultural characteristic.